PENDIDIKAN KEWIRAUSAHAAN DI LAPAS DENGAN PENDEKATAN MINAT USAHA - Sri Hapsari; Dhova Shahroza (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2014)
This descriptive research aimed to discover the implementation of entrepreneurship education that can be developed to be applied at Female Prison, IIB Class, Tangerang. The research conducted as from October 2013 through February 2014 describes the prisoners’ characteristics by age, crime, religion, and education. Besides it also mentions the educational methods applied in the Female Prison. The research stages began with fileld study to obtain data related to education, religion, age, crime, and business interest. The data indicates their interest in commercial business is 71 % with the background of business experience before they were taken into prison and the entrepreneurship education in the prison will motivate them to develop their previous commercial business or to start a business for those who have not done any commercial business.